2022
DOI: 10.1007/s10725-022-00875-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomics reveals key genes contributing to the differences in drought tolerance among three cultivars of foxtail millet (Setaria italica)

Abstract: Comparative transcriptomics reveals key genes contributing to the differences in drought tolerance among three cultivars of Foxtail millet (Setaria italica

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Li et al highlighted the water-saving benefit for millet when rotated with rye [60]. Millet required less soil moisture, and its transpiration efficiency and WUE were much higher than other species (sorghum, maize, and wheat) [64,65]. Yang et al reported that a shallow rooted crop, such as sweet potato, drawing soil moisture from 0-120 cm could preserve deeper soil moisture content for the succeeding deep-rooted crop of winter wheat reaching down to 180 cm or deeper [18].…”
Section: Water Of Diversified Crop Rotationsmentioning
confidence: 99%
“…Li et al highlighted the water-saving benefit for millet when rotated with rye [60]. Millet required less soil moisture, and its transpiration efficiency and WUE were much higher than other species (sorghum, maize, and wheat) [64,65]. Yang et al reported that a shallow rooted crop, such as sweet potato, drawing soil moisture from 0-120 cm could preserve deeper soil moisture content for the succeeding deep-rooted crop of winter wheat reaching down to 180 cm or deeper [18].…”
Section: Water Of Diversified Crop Rotationsmentioning
confidence: 99%
“…The funnel represents the last step of filtering. References [ 62 , 63 , 64 , 65 , 66 , 67 , 68 ] are cited in Supplementary Materials.…”
mentioning
confidence: 99%